Making sense of household accounting amid personal hobbies and breadwinning responsibilities: A phenomenological study of familiy heads - Agustina Riyanti; Nabillah Farras Luthfi (Journal of Law, Administration, and Social Science, 2026)
Starting from the phenomenon of husbands who act as heads of households while still actively pursuing their hobbies, researchers conducted a study aimed at exploring in depth how household accounting works in families with a head of household who is still actively pursuing his hobby and is able to meet household needs. A qualitative approach using Heidegger's phenomenology was used in the study to explore the household's experience in practicing household accounting amid the dynamics of household needs and expenses. The findings of this study show that the head of the household interprets and manages the relationship between meeting household needs and spending on hobbies through a budget based on household priorities and discussions with their spouse. Informants consciously allocate income by prioritizing family needs, while hobbies are placed as personal needs that are limited and adjusted to their roles and responsibilities as husbands. After marriage, there is a shift in the meaning of hobbies from a means of self-fulfillment to a temporary escape from work and home routines, without interfering with their main obligations to the family. Household accounting practices are informal, with short- term and long-term planning developed through discussions with spouses, agreement-based budgeting, and mental record-keeping for constant income and expenses. Another interesting finding is that the wife's support for the informant's hobby strengthens household harmony, while also confirming that household accounting practices from a phenomenological perspective are not solely oriented towards numbers, but rather towards meaning, relationships, and the value of responsibility in family life.